2014
DOI: 10.3945/jn.114.193177
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Emotional Eating and Consumption of Energy-Dense Snack Foods Are Modified by Sex and Depressive Symptomatology

Abstract: In recent years, emotional eating (EmE) has incited substantial research interest as an important psychologic determinant of food intake and overweight. However, little is known about factors that might modulate its relations with dietary habits. The objective of this study was to examine the association between EmE and consumption of energy-dense snack food and assess the 2-way interaction of EmE with sex and depressive symptoms. A total of 7378 men and 22,862 women from the NutriNet-Santé cohort (France, 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
117
2
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(149 citation statements)
references
References 45 publications
16
117
2
14
Order By: Relevance
“…Parental restriction and using food to influence children's behaviors or regulate their emotions (i.e., emotional regulation feeding; Vaughn et al, 2016) during childhood are also associated with emotional eating in college students (Galloway, Farrow, & Martz, 2010;Tan, Ruhl, Chow, & Ellis, 2016). These findings are concerning, given evidence that emotional eating relates to increased fatty food intake and higher body mass index in adults (Camilleri et al, 2014;Cartwright et al, 2003;Konttinen, Mannisto, Sarlio-Lahteenkorva, Silventoinen, & Haukkala, 2010;van Strien, Herman, & Verheijden, 2012).…”
Section: Introductionmentioning
confidence: 80%
“…Parental restriction and using food to influence children's behaviors or regulate their emotions (i.e., emotional regulation feeding; Vaughn et al, 2016) during childhood are also associated with emotional eating in college students (Galloway, Farrow, & Martz, 2010;Tan, Ruhl, Chow, & Ellis, 2016). These findings are concerning, given evidence that emotional eating relates to increased fatty food intake and higher body mass index in adults (Camilleri et al, 2014;Cartwright et al, 2003;Konttinen, Mannisto, Sarlio-Lahteenkorva, Silventoinen, & Haukkala, 2010;van Strien, Herman, & Verheijden, 2012).…”
Section: Introductionmentioning
confidence: 80%
“…For example, Wouters et al (14) found that snacking and soft drink intake was more prevalent in boys and less-educated youth. In addition, emotional eaters and individuals under psychological stress have been found to consume higher amounts of energy-dense snacks, particularly sweet and fatty snacks (15). Moreover, knowledge about healthful snacks and self-efficacy in choosing the "right" snacks are important determinants of snacking behavior (16).…”
Section: Determinants Of Snackingmentioning
confidence: 99%
“…Emotional eating leads to an unhealthier diet since it is suggested that food with high energy density can ameliorate negative affect or stress (89) . As a result, emotional eating increases the intake of sweet and fatty foods, or 'comfort food' (90)(91)(92) . In experimental studies, emotional eaters have been found to consume more sweet and fatty foods (93)(94)(95) in response to stress.…”
Section: Nutrition Research Reviewsmentioning
confidence: 99%